Viejas y nuevas cuestiones de lengua en el occidente peninsular: el lusitano y la onomástica (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In this article I outline a synthesis of some works on the peninsular West that, as regards linguistics, have been published in the last years. The scholars are under the impression that Celtic people coexisted with non-Celtic people. Some authors have even seen the existence of more than a Celtic group and, likewise, more than a non-Celtic group. In any case, in order to advance in common views, I propose marking out landscapes as much of Lusitanian language as personal names, deity names or place  names, with the purpose of looking for elements that show a common distribution. That will allow us to characterize linguistically a uniform landscape, in the same way that other peninsular areas like Celtiberian or the Iberian.
Keywords: Peninsular West; Lusitanian; personal names; deity names; toponymics